Efisiensi dan Efektivitas Penggunaan Uang Elektronika (E-Money) dalam Inovasi Pengembangan Bisnis - Verry Albert Jekson Mardame Silalahi; Audrey Gamaliel Dotulong Tangkudung (UniSadhuGuna Business School, 2024)
E-Money, or electronic money, has become a significant electronic payment instrument in the digital era, changing the way financial transactions are conducted and influencing business and the global economy. This study explores the impact of using E-Money in business development and the digital economy. His background includes the important role of E-Money in the financial transaction revolution and its impact on global markets. The research objective is to evaluate the efficiency and effectiveness of using E-Money in business innovation, as well as analyzing its impact on the digital economy. Research methods involve analysis of technology, regulations, and business impacts. The research results show that the use of E-Money provides innovative solutions for digital transactions, increases operational efficiency and reduces transaction costs. However, challenges also arise regarding security, data privacy and accessibility. In conclusion, E-Money has great potential to transform business operations and the global economy, with significant impacts on innovation, operations and policy. The integration of E-Money in business strategy can increase overall innovation and efficiency, although it is necessary to pay attention to the challenges that arise along with its use.